2017
DOI: 10.1155/2017/8562329
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Cam and Pincer Deformities in the X-Rays of Asymptomatic Individuals

Abstract: Objective The presence of radiological signs of femoroacetabular impingement (FAI) is not necessarily associated with symptoms. Hence, the prevalence of cam and pincer deformities in the overall population may be underestimated. The purpose of this study was to screen an unselected cohort of people without hip symptoms for native radiological signs of cam and pincer deformities to determine their actual prevalence. Materials and Methods 110 asymptomatic patients had AP pelvis X-rays and cross-table hip X-rays … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 44 publications
1
5
0
1
Order By: Relevance
“…The results showed 82 patients (71.9%) with at least one radiological sign of cam or pincer deformity, 52 patients (45.6%) showed two, and 18 patients (15.8%) showed three; none of the patients showed more than three signs. 17 Here the overall prevalence of FAI 15.8% is comparable to our present study. Positive cross-over signs were seen in 34%.…”
Section: Discussionsupporting
confidence: 89%
“…The results showed 82 patients (71.9%) with at least one radiological sign of cam or pincer deformity, 52 patients (45.6%) showed two, and 18 patients (15.8%) showed three; none of the patients showed more than three signs. 17 Here the overall prevalence of FAI 15.8% is comparable to our present study. Positive cross-over signs were seen in 34%.…”
Section: Discussionsupporting
confidence: 89%
“…For example, a significantly lower femoral version of 15 ° has been demonstrated in patients with symptomatic Cam-FAI compared to asymptomatic controls (22°) [ 30 ]. Cam deformities have also been found in a considerable proportion of asymptomatic individuals [ 18 , 57 ]. Furthermore, Gramamtopoulos et al suggested that acetabular version may be one factor leading to the development of symptoms in patients with a cam deformity, showing a significantly higher acetabular version of 17 ° in symptomatic cam patients, compared to 11 ° in asymptomatic cam controls [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…FAI is a cause of early hip dysfunction that can lead to secondary osteoarthritis. An association between presence of FAI and development of osteoarthritis has been reported, but there are asymptomatic patients with radiological findings suggestive of FAI reported in other studies3419222829). Cam impingement is due to a femur-based deformity associated with loss of spherecity of the femoral head, reduced head neck offset ratio and retroverted neck.…”
Section: Hip Injectionmentioning
confidence: 94%